Are consumers willing to pay for a product processed by emerging technologies? The case of chocolate milk drink processed by cold plasma. (March 2021) - Coutinho, Nathalia M.; Silveira, Marcello R.; Guimarães, Jonas T.; Fernandes, Leonardo M.; Pimentel, Tatiana C.; Silva, Marcia C.; Borges, Fábio O.; Fernandes, Fabiano A.N.; Rodrigues, Sueli; Freitas, Monica Q.; Esmerino, Erick A.; Cruz, Adriano G.
Abstract: This study aimed to evaluate the consumers' perception (n = 1085) about processing chocolate milk drinks by cold plasma. The consumers were asked about food technology neophobia, familiarity and, willingness to buy the product, sensory attributes, and perceived quality compared to traditional technologies. The consumers considered that new technologies could have a negative impact on health, natural quality of the product, and environment, that the benefits of the new technologies are overstated, and that could be a risk replacing the traditional technologies. However, most of the consumers (72.3%) were willing to buy the chocolate milk drink processed by cold plasma, mainly if the price is similar to that of the conventional product. Chocolate milk drink should have a brown color, chocolate flavor, typical chocolate and milk taste, and high consistency. The willingness to buy the new product increases with the belief that the new technologies would not bring negative health effects, while it decreases with the unfamiliarity with new technologies, doubts about the information provided by the media, or no perceived quality compared to the traditional technology. Therefore, it is important that the food industry provide consumers with trustable, understandable, and clear information so that the lack of confidence could be overcome. Highlights: Consumer perception of chocolate milk drink processed by cold plasma. The benefits of the new technologies are overstated. Consumers appreciate brown color, chocolate and milk taste, and high consistency. Information about effect on the health increases the willingness to pay. Trustable, understandable, and clear information for consumers are required.